Strategi dan Arahan Pengembangan Infrastruktur Objek Wisata untuk Meningkatkan Daya Tarik dan Keberlanjutan Pantai Kampe - Emely, Shofi Nindia; Soetjipto, Jojok Widodo; Listyawati, Ratih Novi (Jurnal Spesialis Teknik Sipil (JSpTS), 2025)
Infrastructure plays an important role in developing regions, particularly in the economic, social, cultural, and environmental aspects. One of the regions experiencing development is Banyuwangi Regency, particularly in the tourism sector, as it has the greatest tourist attractions, thus having the potential to support economic growth. Kampe Beach is one of the designated tourism areas with natural tourist attractions in Banyuwangi Regency. Based on the 2012-2032 Banyuwangi Regency Spatial Plan, Kampe Beach is included in the Tourism Development Area (WPP) I. The infrastructure owned by Kampe Beach is still inadequate and there are several supporting tourism infrastructures that are not yet available. Therefore, there is a need for infrastructure development directions that can support tourism activities at Kampe Beach so that it can assist the Banyuwangi Regency government in developing the region. This study aims to determine the existing condition of Kampe Beach and the level of importance and performance of Kampe Beach infrastructure so that directions for Kampe Beach infrastructure development can be formulated to support the tourism sector in Banyuwangi Regency. The methods used in this study are descriptive analysis to identify existing conditions, the Importance-Performance Analysis (IPA) method to determine the level of importance and performance of each research variable, and triangulation analysis to formulate infrastructure development directions. This study determined the sample using the Lemeshow formula and produced 67 respondents to determine the level of importance and performance of the predetermined variables. The results of the study indicate that infrastructure that requires development directions is located in quadrant I consisting of waste, road networks, road signs, parking lots, and security posts. Development directions that need to be carried out at the research location include conducting socialization and training, procuring infrastructure that is not yet available, and placing road signs more strategically.